Reimagining AI for sustainability: Cultivating imagination, hope, and response-ability - Hultin, Lotta; Mähring, Magnus (Information and organization, 2025)
While the use of Artificial Intelligence (AI) in sustainability efforts continues to grow, dominant approaches remain narrowly focused on optimization, prediction, and control. This paper challenges the predictive/optimizing paradigm by proposing a relational perspective on AI—one that treats uncertainty not as a problem to eliminate, but as a generative space for creativity, care, and transformation. Drawing on theories of relational agency, imagination, and hope, we explore how AI can participate in co-creating more ethical, empathetic, and ecologically attuned practices. Leveraging a preexisting case of AI-driven wildlife management in India, we conduct an analysis of a possible and desirable future, demonstrating how AI's affordances might be reconfigured and expanded: from tools of surveillance and efficiency to invitations for listening, attunement, and world-making. In this reimagined mode, AI supports not only the processing of data but the emergence of stories—enabling practitioners to sense, interpret, and respond to ecological entanglements in ways that foreground more-than-human perspectives and collective vulnerability. We contribute to the growing discourse on sustainable AI by theorizing how practices of imagination and hope can cultivate response-able agency—a form of ethical responsiveness grounded in interdependence rather than mastery. Ultimately, we call for a reorientation of AI design and governance toward practices that do not merely optimize what is, but help bring forth what could be. •We call for moving beyond the dominant predictive/optimizing paradigm on AI for sustainability, and propose a relational perspective on AI that treats uncertainty not as a problem to eliminate, but as a generative space for creativity, care, and transformation.•Building on an existing case of the use of AI in wildlife management in India, we conduct an analysis of a possible and desirable future, demonstrating how AI’s affordances might be reconfigured and expanded: from tools of surveillance and efficiency to invitations for listening, attunement, and world-making•Employing imagination allows us to transcend the limitations of the present, inviting us to co-create with AI and the environment, and cultivating hope opens up space for acknowledging the inherent uncertainty and indeterminacy of the future. Together with ethical responsiveness, this allows for using AI to go beyond incremental solutions, and toward desirable futures, in addressing sustainability challenges•We contribute to the growing discourse on sustainable AI by theorizing how practices of imagination and hope can cultivate response-able agency—a form of ethical responsiveness grounded in interdependence rather than mastery.